Different worlds of athlete welfare? A social policy perspective on elite sport in six European countries - Seltmann, M. (International Journal of Sport Policy and Politics, 2025)
Governments of all European countries vie for international sporting success, with elite athletes typically participating in national elite sport programmes coordinated by both public and private entities. Recent research sheds light on the precarious social conditions that many elite athletes endure, marked by low income and social protection gaps. This article examines athlete welfare within the context of social policy by assessing athletes` access to income opportunities and social protection coverage. The case-oriented comparative study explores the legal frameworks and policies for athlete welfare in six European countries and inductively establishes five ideal-type governance models of athlete welfare. The classification of cases according to the models reflects the interplay between a country`s welfare regime and its national sport policy system in this specific policy subfield. The findings highlight common effects of the different models on athletes` social conditions and livelihoods and emphasise employment status as a crucial factor for their welfare.